PIK3CA and PIK3R1 tumor mutational landscape in a pan-cancer patient cohort and its association with pathway activation and treatment efficacy - Zoé Tharin; Corentin Richard; Valentin Derangère; Alis Ilie; Laurent Arnould; François Ghiringhelli; Romain Boidot; Sylvain Ladoire (Scientific Reports, 2023)
Abstract There is little data concerning the implications of PIK3CA mutations outside of the known hotspots described in ER+/HER2− metastatic breast cancer (mBC). Similarly, PIK3R1 mutations could also lead to activation of PI3K pathway, but are poorly described. We determined the incidence and type of all somatic PIK3CA and PIK3R1 mutations by whole exome sequencing (WES) in a pan-cancer cohort of 1200 patients. Activation of the PI3K pathway was studied using phospho-AKT immunohistochemistry. Associations between PIK3CA/PIK3R1 mutations and response to chemotherapy were studied in mBC cases. We found 141 patients (11.8%) with a PIK3CA and/or PIK3R1 mutation across 20 different cancer types. The main cancer subtype was mBC (45.4%). Eighty-four mutations (62.2%) occurred in the three described hotspots; 51 mutations occurred outside of these hotspots. In total, 78.4% were considered activating or probably activating. Among PIK3R1 mutations, 20% were loss of function mutations, leading to a constitutional activation of the pathway. Phospho-AKT quantification in tumor samples was in favor of activation of the PI3K pathway in the majority of mutated tumors, regardless of mutation type. In ER+/HER2− mBC, first line chemotherapy efficacy was similar for PIK3CA-mutated and PIK3CA-WT tumors, whereas in triple negative mBC, chemotherapy appeared to be more effective in PIK3CA-WT tumors. In this large, real-life pan-cancer patient cohort, our results indicate that PIK3CA/PIK3R1 mutations are widely spread, and plead in favour of evaluating the efficacy of PI3K inhibitors outside of ER+/HER2− mBC and outside of hotspot mutations.